Subterranean species of Acipes Attems, 1937 (Diplopoda, Julida, Blaniulidae) - Enghoff, Henrik; Reboleira, Ana Sofia P. S. (Zootaxa, 2013)
Two new blind, cave-dwelling species of the genus Acipes Attems, 1937, are described from the Algarve, southern Por-tugal: A. machadoi n. sp. and A. bifilum n. sp. Acipes andalusius Enghoff & Mauriès, 1999, is reported from the mesovoid shallow substratum in Alicante (Spain), 250 km from the type locality in Andalusia.